Optimal fiscal policy in a model with search-and-matching frictions: the case of Bulgaria (1999-2018) - Aleksandar Vasilev (Post-Communist Economies, 2020)
This paper explores the effects of fiscal policy in an economy with search and matching frictions. To this end, a dynamic general-equilibrium model with government sector is calibrated to Bulgarian data (1999-2018). Two regimes are compared and contrasted - the exogenous (observed) vs. optimal policy (Ramsey) case. The focus of the paper is on the relative importance of consumption vs. income taxation, as well as on the provision of utility-enhancing public services. The main findings from the computational experiments performed in the paper are: (i) The optimal steady-state income tax rate is zero; (ii) The benevolent Ramsey planner provides the optimal amount of the utility-enhancing public services, which are now three times lower; (iii) The optimal steady-state consumption tax needed to finance the optimal level of government spending is 18:3%, slightly lower than the rate in the exogenous policy case.
Keywords: E24; E32; 330; optimal (Ramsey) fiscal policy; general equilibrium; unemployment and wages; Bulgaria